2016
DOI: 10.1038/jes.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error in mobile source air pollution exposure estimates due to residential mobility during pregnancy

Abstract: Prenatal air pollution exposure is frequently estimated using maternal residential location at the time of delivery as a proxy for residence during pregnancy. We describe residential mobility during pregnancy among 19,951 children from the Kaiser Air Pollution and Pediatric Asthma Study, quantify measurement error in spatially-resolved estimates of prenatal exposure to mobile source fine particulate matter (PM2.5) due to ignoring this mobility, and simulate the impact of this error on estimates of epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Consistent with prior research [ 29 , 32 , 43 ], our analyses revealed statistically significant associations between exposure to both NO 2 and PM 2.5 in early life and subsequent childhood asthma risk, both before and after adjustment for relevant covariates ( Table 2 and Table 3 ). Because SD and IQR rescaling of the pollution variables produced substantively equivalent results, we present only the IQR-rescaled estimates throughout; though the SD-rescaled results are available in the supplemental material (supplemental Tables S1–S3) .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with prior research [ 29 , 32 , 43 ], our analyses revealed statistically significant associations between exposure to both NO 2 and PM 2.5 in early life and subsequent childhood asthma risk, both before and after adjustment for relevant covariates ( Table 2 and Table 3 ). Because SD and IQR rescaling of the pollution variables produced substantively equivalent results, we present only the IQR-rescaled estimates throughout; though the SD-rescaled results are available in the supplemental material (supplemental Tables S1–S3) .…”
Section: Resultssupporting
confidence: 90%
“…This study aims to contribute to this body of literature by examining childhood asthma as a function of exposure to air pollution during the prenatal and early postnatal periods using spatially- and temporally-resolved air pollution measures and a population-based, multilevel, longitudinal study of US children and their families. Consistent with prior research that found associations between prior pollution exposure and future asthma risk [ 29 , 32 , 43 ], our analyses reveal that the odds of future asthma diagnosis for children exposed to a high concentration of NO 2 in early life are 1.25 times greater than those for children exposed to a low concentration of NO 2 . We also find that an interquartile increase in early-life exposure to PM 2.5 (4.43 µ/m 3 ) increases the odds of future childhood asthma risk by a factor of 1.25.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although there is imprecision in the date of address change, simulations performed using KAPPA data to investigate the consequences of exposure measurement error due to residential mobility suggest that in this cohort this source of error likely causes only a small (2–10%) bias towards the null 31 . The calibrated RLINE estimates were shown in Zhai et al (2016) to have good accuracy and precision; the calibration reduced normalized mean bias for all pollutants when compared to raw RLINE estimates (29% to 0.3% for PM 2.5 , 22% to −1% for CO, and 303% to 43% for NO x ).…”
Section: Discussionmentioning
confidence: 90%
“…Another limitation of our study is that we were unable to capture maternal mobility because only the birth mother's place of residence at the time of birth is recorded in the birth records. Prior studies have suggested that ignoring residential mobility may bias associations toward the null due to nondifferential exposure misclassification, and that moving distances during pregnancy are typically relatively short and within the same county (Bell and Belanger 2012;Chen et al 2010;Hodgson et al 2015;Lupo et al 2010;Miller et al 2010;Pennington et al 2017).…”
Section: Discussionmentioning
confidence: 99%